Design of a Visual Basic HEC-RAS interface to test influence of daily regulation of a hydropower plant on navigation - Peter Šulek; Martin Orfánus (Discover Applied Sciences)
Abstract The Hydrologic Engineering Center River Analysis System (HEC-RAS) software package developed by the U.S. The Army Corps of Engineers is a widely used software package designed mainly for modeling steady and unsteady water flow in rivers. Although the software includes tools for implementing basic control elements, HEC-RAS users often require additional unique functions including integration with other software. This is made possible by means of the HEC-RAS Controller, an application programming interface (API) that allows manual interaction with HEC-RAS to enable automated control through user-defined code directly from other programming environments. The main goal of this study was to design a universal software architecture for linking HEC-RAS with Visual Basic using the API, which enables users to enter the unsteady flow boundary condition directly as the demand power output if the river system under analysis includes a hydropower plant. The effectiveness of the proposed approach and its applicability to real-world operational management environments were demonstrated through a case study of the Gabčíkovo hydropower plant on the Danube River in Slovakia. The integration of the HEC-RAS with Visual Basic enabled the simulation of the Danube River's water-level regime within a reasonable time and with adequate accuracy, allowing for the analysis of the impact of daily flow regulation on navigation conditions downstream of the hydropower plant.